(untitled) (Fiep Bulletin - online, 2014)
Agility, speed and endurance are integral aspects of almost every defensive and offensive m?noeuvre performed by football players in practices and games. Testing for assessing motoric fitness levels of team players is an essential component in the evaluation of training programs and the assessment of players` progress during the season. The aim of this research is to define model of tendency of changes in speed, agility and endurance in young and perspective football players as a result of football training system in Serbia. 290 young football players (Ages 12 N= 73, ages 13 N= 98, ages 14 N= 65, ages 15 N= 54) performed a standardized specific field tests in order to assess speed (10 m quickness, flying 20m sprint and 30 m sprint), agility (zigzag test with and without ball) and endurance (YO YO intermittent test) performances. All the results were processed applying the descriptive statistics, multivariate analysis and the tendency of changes in the observed contractile characteristics was afterwards defined by applying the method of linear regression using the general equation: y = abx. Multivariate statistical analysis established that there is a significant difference at all observed performance at the level of Wilks´ Lambda 0.464, F=13.788, p=0.000, among the observed sub-samples. Statistically significant difference was also established at allvariables regarding the observed sub-samples. Besides, the results showed the statistically significant (p=0.000) tendency of change in all tested performance tests. Generally, obtained differences between observed age categories and presented model of tendency of changes can serve as criteria for any future sports training technology improvement according to young football players as well as considering long term planning process.